2007
DOI: 10.1523/jneurosci.4791-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural Amino Acid Mutagenesis of the GABAAReceptor Binding Site Residues Reveals a Novel Cation–π Interaction between GABA and β2Tyr97

Abstract: The binding pockets of Cys-loop receptors are dominated by aromatic amino acids. In the GABA A receptor ␣ 1 Phe65, ␤ 2 Tyr97, ␤ 2 Tyr157, and ␤ 2 Tyr205 are present at the ␤ 2 /␣ 1 interface and have been implicated in forming an important part of the GABA binding site. Here, we have probed interactions of these residues using subtle chemical changes: unnatural amino acid mutagenesis was used to introduce a range of Phe analogs, and mutant receptors expressed in oocytes were studied using voltage-clamp electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 30 publications
4
125
0
2
Order By: Relevance
“…The data include not only fluorinated analogs, but also a Phe derivative with a cyano group (CN) in the 4 position. 4-CN-Phe is slightly larger in size than the fluorinated Phe derivatives but is well tolerated in Cys-loop receptor binding sites (Padgett et al, 2007;Pless et al, 2008). This substitution yielded a ␤-alanine EC 50 between those for 3,4-F 2 -Phe and 3,4,5-F 3 -Phe, consistent with the cation-binding ability of 4-CN-Phe.…”
Section: Downloaded Frommentioning
confidence: 63%
See 2 more Smart Citations
“…The data include not only fluorinated analogs, but also a Phe derivative with a cyano group (CN) in the 4 position. 4-CN-Phe is slightly larger in size than the fluorinated Phe derivatives but is well tolerated in Cys-loop receptor binding sites (Padgett et al, 2007;Pless et al, 2008). This substitution yielded a ␤-alanine EC 50 between those for 3,4-F 2 -Phe and 3,4,5-F 3 -Phe, consistent with the cation-binding ability of 4-CN-Phe.…”
Section: Downloaded Frommentioning
confidence: 63%
“…Like all Cys-loop receptors, the GlyR binding site is lined with aromatic residues, and we have shown previously that a cation-interaction between the positively charged amine of glycine and Phe159 in loop B makes a substantial contribution to agonist binding (Pless et al, 2008). Likewise, other studies have shown that aromatic side chains form cationinteractions with the principal agonists of other Cys-loop receptors, such as nACh, 5-HT 3 , MOD-1 (modulation of locomotion defective 1), and GABA A receptors (Zhong et al, 1998;Beene et al, 2002;Mu et al, 2003;Lummis et al, 2005;Padgett et al, 2007;Dougherty, 2008). However, the nature and location of the aromatic residue that interacts with the cation is not conserved among Cys-loop receptors or among different agonists for a given receptor (Beene et al, 2002;Mu et al, 2003;Dougherty, 2008;Xiu et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Mutation of the homologous W55 residue in the GABA A -R ␥2-subunit, F77C, abolished binding by (28). In the GABA A -R ␣1-subunit, it was shown that for the homologous Trp-55 subtle changes were caused by unnatural amino acid mutations (29). In the muscle nAChR it was shown that mutation W57F in the ␦-subunit and W55F in the ⑀-subunit have only minor effects on acetylcholine-sensitivity but mainly affect channel gating by reducing the channel opening rate (30).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in nicotinoids, one fundamental bound conformation is conserved for all AChBP and nAChR subtypes (7)(8)(9)(10)23). The same agonist molecule can also adopt different binding orientations at other Cys-loop receptors, depending on the nature and position of aromatic amino acid side chains, that is, serotonin (5-HT) at 5-HT 3 versus MOD-1 receptors and ␥-aminobutyric acid (GABA) at GABA A versus GABA C receptors (24,25).…”
Section: Discussionmentioning
confidence: 99%